Operation of a SiC-Based Three-Phase PFC Converter in an Industrial DC Conductor System with Distributed DC Link Capacitors - Koch, Jan-Niklas; Otte, Raphael; Borcherding, Holger (PCIM Europe 2022 : International Exhibition and Conference for Power Electronics, Intelligent Motion, Renewable Energy and Energy Management : 10-12 May 2022)
In this paper a highly efficient three-phase power factor correction (PFC) converter is used as an active infeed converter (AIC) for an industrial DC conductor system. The DC grid is a monorail conveyer system with distributed DC link capacitors and intelligent energy storages alongside the conductor. The operation of the system, using voltage droop control for proper load distribution, is investigated. The power consumption of the proposed DC grid will be compared to a conventional AC grid with identical drives. The used active infeed converter operates at 100kHz and 650V nominal DC bus voltage with a nominal power of 5kW.